The Paradigm Shift of the Legal Eduv=cation in Malaysia: A Research on the Global Perspective - Mohd Fuad, Husaini; Kamaliah, Salleh (2013)
The professional training of law graduates in Malaysia has intersects with multiple avenues into the legal profession requiring variant standards of admittance. This scenario has instigated the need to remonstrate the existing state of affairs. Therefore, there has been a great urge by the Bar Council prompting a Common Bar Course (CBC) an90d Examination (CBE) marshalling a new direction in the training of law graduates for legal practice to become a single entry point into the legal profession for both local and foreign law graduates. However, the path to the implementation of CBE into the legal education is not as attractive as it is thought it would be, referring to the amount of effort needed to progress along the way. It has been an ongoing debate among the law practitioners on whether it should be implemented or vice versa, considering some substantial factors. This article begins with the introduction of the legal education in Malaysia. Secondly, it analyses the current entry requirements into the legal profession and how it fair with the standards across the Commonwealth jurisdictions. Thirdly, it examines the global development of legal education systems, the legal framework of CBC together with the justifications by the proponents and the objections raised against such proposal. Then this article attempts to deliberate on the need of the reformation of the legal education in tandem with the global development of legal education across common jurisdictions. Finally the article concludes on the viability of the CBC proposal or any other proposal to resolve the legal education debacle in Malaysia.